Alpha-1 Antitrypsin Deficiency-Associated Clinical Manifestations and Healthcare Resource Use in the United States - Ernesto Mayen Herrera; Corey Joseph; Emily S. Brouwer; Vivek Gandhi; Michael Czorniak (COPD, 2021)
Pulmonary events (PEs) associated with alpha-1 antitrypsin deficiency (AATD) can have a severe clinical course and increase healthcare resource use (HRU). However, AATD-associated HRU and healthcare costs have not been extensively described. This study describes and compares real-world HRU and healthcare costs among US patients with severe (requiring hospitalization after AATD-related PE) versus nonsevere AATD clinical course. Administrative healthcare claims for patients with a second primary AATD diagnosis between 6/1/2008 and 12/31/2017 were analyzed from 2 databases (requiring continuous enrollment 6 months preceding diagnosis). Patient baseline characteristics and AATD-associated PE incidence rates, HRU, and healthcare costs during follow-up were compared in patients with severe versus nonsevere AATD. Of 5109 patients with a second AATD diagnosis, 2674 (severe, n = 711 [26.6%]; nonsevere, n = 1963 [73.4%]) had ≥1 AATD-associated PE. PE incidence per 100 person-years was higher in patients with severe versus nonsevere AATD. Annual incidences (mean ± SD) of emergency department (1.2 ± 5.7 vs. 0.4 ± 1.2), inpatient (1.3 ± 2.5 vs. 0.1 ± 0.5), and outpatient (10.3 ± 15.9 vs. 5.7 ± 13.2) visits were higher in patients with severe versus nonsevere AATD. Median (interquartile range) annual costs were also higher for patients with severe versus nonsevere AATD for emergency department ($185 [$0–$1665] vs. $0 [$0–$264]), inpatient ($16,038 [$2968–$70,941] vs. $0 [$0–$0]), and outpatient ($2663 [$412–$10,277] vs. $1114 [$134–$4195]) visits. Higher percentages of patients with severe AATD were prescribed augmentation therapy, antibiotics, or corticosteroids. These findings suggest that patients with severe AATD have higher incidence of AATD-associated PEs, as well as higher HRU and healthcare costs.